Voyage en Russie : de Paris À Saint-Pétersbourg - Alexandre Dumas (NC, 1950)
304 p. ; 21 cm | Originally published as part of the author's De Paris à Astrakan
Source a verifier sur Internet Archive
Keywords: alexandre dumas